(untitled) - AYU WIDYA NINGRUM, AGUSTINA (Jurnal Pendidikan Tata Niaga (JPTN), 2014)
As era development and technology trend people life in terms of health especially in the area of medicine seemed experiencing shift or change, from treatment modern toward traditional medicine. Transactional lifestyle “back to nature” is leading to competition in industry jamu this is tight and the lenght. Many companies should competition is making rapid and proper in determining marketing strategies taken.One strategy right is undertaken by a corporation strategy of marketing communications media advertising.Usually in companies advertise is endorsed by ditelevisi is use to promote their products, at once it can use a captivating consumers. Business company use a endorser also meant to affect consumers, so consumers interested in buying products advertised. On this research, researchers used causal the kind of research and the data analyzed quantitatively.Population to be used in the research even all students economics faculty unesa based on certain criteria, hence population sizes in research this being intangible ( infinite ) and samples as much as 385 respondents, by using accidental sampling. The result showed that there are significant influence of a variable credibility ( X1 ), attractiveness ( X2 ), and power ( X3 ) against interest purchase ( y ) Tolak Angin of 0.495 or 49.5%, while the remaining 50,5% is affected by other variable. The power variable is dominant variable with grade tarithmetic is 11,477. Keywords: Endorser, Credibility, Attractiveness, Power, Purchase Interest.